Bandung Conference Revisited: Comparative Analysis of Soekarno’s an Retno Marsudi’s Diplomatic Approaches to Palestine - Arum Rumaesih; Firdan Fadlan Sidik (Publication of the International Journal and Academic Research, 2025)
The Asia-Africa Conference of 1955, or the Bandung Conference, was a historic meeting that aimed to articulate and support independence movements across Asia and Africa. During the conference, Soekarno placed Palestine as a top priority, extending Indonesia's support based on national interest and the broader struggle against prolonged colonialism. The Bandung Conference became a milestone in Indonesia's foreign diplomacy, a legacy later reaffirmed by Foreign Minister Retno Marsudi in her 2023 United Nations General Assembly address. This paper explores the underlying philosophy of the Bandung Conference by analyzing Soekarno's political stance on Palestine from the early twentieth century onwards. Using primary sources including Indonesian historical records and Dutch newspapers, the study maps out the principles of the Bandung Conference and examines how these principles appear in Marsudi's diplomatic advocacy. The paper questions whether Marsudi merely invoked the Bandung Spirit rhetorically or translated it into concrete action. The findings show that the values of the Bandung Conference were deeply rooted in a critical understanding of colonialism and accompanied by intellectual debate and transnational advocacy. The study demonstrates how these foundational ideas have extended into tangible aspects of Indonesian foreign policy. Ultimately, the article concludes that Retno Marsudi's advocacy efforts align with the legacy and values of the Bandung Conference.